Implementasi Pembelajaran Kewirausahaan Berbasis Proyek Untuk Meningkatkan Daya Tarik dan Berpikir Kreatif Siswa di SMPN 3 Blitar - Syahrul Hikam; Nafa Amalina; Cindy Aurelia Wahyudi; Kharisma Mutiara Aisyah; Alfan Mardianto; Dewi Puspa Arum (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This study aims to explain entrepreneurship learning and gain an understanding of the process of implementing entrepreneurship learning in increasing the attractiveness and creative thinking of students at SMP Negeri 3 Blitar. The research subfocus consists of 1). Learning models in improving the character of the entrepreneurial spirit of SMP Negeri 3 Blitar students, 2). The contribution of East Java